Conversion Rate Optimization with A/B Testing - Pařízek, Michal (2010)
The goal of this Master's thesis is to explain the importance of the Conversion Rate Optimization (CRO) at today's E-commerce market share. A lot of people in Czech Republic confuse this term with more popular and similar term: Search Engine Optimization (SEO). The CRO focuses on the particular website and its ability to meet the business goals. The goal of the CRO is to improve the website and its conversion rates for acceptable costs. The ROI is important here. The CRO is a broad topic so I focus only on one part -- A/B Testing. This technique is based on showing different variations of a specific web page to the users. They are divided among these variations. Each part can see different variation. In the result we can see which variation was the best in meeting the business goals. The goal of this Master's thesis is to thoroughly introduce this technique and the tool which is perfectly suitable for that -- Google Website Optimizer. It is free and worldwide known and used. This Master's thesis is divided into several main chapters. In the introduction I describe few marketing models that are closely related to the CRO. Then I focus on the CRO, A/B Testing and Google Website Optimizer. In the last chapter you can find a case study full of practical examples. So far there are only a few resources about CRO in the Czech language. That also demonstrates the fact, that the CRO is not much popular in Czech Republic so far. On the contrary in the USA or Western Europe these techniques are commonly used. Not only big companies like Google or Amazon.com, but even small businesses use the techniques of CRO and can profit from it. I think it is only the matter of time it becomes more popular also in the Czech Republic. Therefore I believe a lot of people find my Master's thesis very useful.